Collaborative Governance and Public Policy on Sexual Violence in Malang City - Watiningsih, Erna; Kamil , Muhammad (Laboratorium Administrasi Publik FISIP Universitas Andalas, 2025)
This study examines the implementation of collaborative governance in addressing sexual violence cases in Malang City, a pressing issue that disproportionately affects women and children. The research is driven by the persistence of patriarchal cultural norms and weak parental supervision, which exacerbate the problem. Employing a qualitative approach, data were collected through field observations and in-depth interviews with government agencies, psychologists, and civil society organizations. Analysis was conducted using Ansell and Gash’s collaborative governance framework in conjunction with Creswell’s data analysis model. The findings indicate that collaborative governance, coordinated by the Department of Social Affairs P3AP2KB, strengthens service integration by providing psychosocial assistance and legal support to victims. The study underscores that multi-stakeholder partnerships are essential for ensuring access to justice and effective victim protection. From a policy perspective, the results demonstrate that sustained institutional synergy, active participation, and resource sharing are prerequisites for effective collaborative governance. The study offers practical insights for local governments in Indonesia seeking to design collaborative mechanisms capable of responding to complex social issues such as sexual violence.